Activities of the wintering party of the 22nd Japanese Antarctic Research Expedition in 1981-1982 - Yoshio Yoshida (National Institute of Polar Research, 1984)
Thirty-four men of the wintering party occupied Syowa Station and Mizuho Station from February 1,1981 to January 31,1982,carrying out observations in many scientific disciplines, particularly laying emphasis on "Polar Experiment-South (POLEX-South)" and on "The studies of crustal structure of the Lutzow-Holm Bay region" whose programs cover the last phase of the two threeyear projects. In the POLEX-South project, micro-meteorological and aerological observations were carried out in the inland plateau during the oversnow traverses, as well as micro-meteorology at Mizuho Station. Glaciological studies were also conducted at the same time. The studies of crustal structure consist of aeromagnetic survey, gravity measurement, heat flow measurement, ground-tilt measurement, and submarine geology and geomorphology. Meteorite search and glacial geomorphological survey were also carried out. In addition, aerial photography covered 80% of the Sor-Rondane Mountains region. At Syowa Station, besides the routine observations of aurora, geomagnetism, ionosphere, meteorology, seismology, and ocean tide, the studies of upper atmosphere physics including geophysical data reception from scientific satellites, environmental pollution, and medical science were conducted. In particular, the data aquisition system in the upper atmosphere physics was greatly improved, introducing the computer processing system and the data telemetering system from the newly-built automatic station about 4km apart from the main base.